Characterization of the melt removal rate in laser cutting of thick-section stainless steel - Wandera, Catherine; Kujanpaa, Veli (Journal of Laser Applications, 2010)
The efficiency of the laser cutting process depends on both the rate of melting and rate of melt removal from the cut kerf. The depth of flow separation and the dross attachment on the lower cut edge relate to the efficiency of the melt removal process and can be used to characterize the rate of melt removal from the cut kerf. The melt flow velocity and melt film thickness are formulated in this study by consideration of the fundamentals of viscous incompressible fluid flow. The calculated melt flow velocity and melt film thickness are correlated with the depth of flow separation on the 10 mm stainless steel AISI 304 EN 1.4301 laser cut edge. The effects of process parameters—including assist gas pressure, nozzle diameter, nozzle standoff, focal point position, and cutting speed—on the depth of flow separation and the dross attachment on the lower cut edge are investigated. The assist gas pressure, nozzle diameter, and focal point position are found to significantly affect the efficiency of melt removal from the cut kerf.
Keywords: Laser cutting; Melt removal rate; Thick-section stainless steel; Melt velocity; Boundary layer thickness; Flow separation